How Big is the Brain Drain? - Carrington, William (IMF Working Papers; Working Paper ;, 1998)
The brain drain from developing countries has been lamented for many years, but knowledge of the empirical magnitude of the phenomenon is scant owing to the lack of systematic data sources. This paper presents estimates of emigration rates from 61 developing countries to OECD countries for three educational categories constructed using 1990 U.S. Census data, Barro and Lee's data set on educational attainment, and OECD migration data. Although still tentative in many respects, these estimates reveal a substantial brain drain from the Caribbean, Central America, and some African and Asian countries.